Power why some people have it--and others don?t - Pfeffer, Jeffrey (New York HarperBusiness, 2010)
"The summa of one of the greatest minds in management theory, this book shows readers how to succeed and wield power in the real world
Includes bibliographical references and index.
Keywords: Success in business